When is carbon monoxide most dangerous - Safety concerns at Festivals - Nyombi, Antony; Williams, Mike; Wessling, Roland (Cranfield University, 2017)
This study investigated the effect of temperature & air flow on CO evolved from barbecue charcoal. The amounts of CO were analysed using FTIR and Electrochemical sensors and the colours of charcoal at different temperatures were analysed with reference to a black body radiator. Results show that carbon conversion increased linearly with temperature. CO evolution started at a point when the charcoal was still black. Maximum amounts of CO were recorded at 400-450 deg C but these then reduced as temperatures rose to 600 deg C. Air flow had little effect on carbon conversion and the amounts of CO evolved. Temperature played a dominant but not linear role in CO evolution. Charcoal attained a reddish colour visible to the naked eye at 550 deg C. This intensified to glowing red at higher temperatures. These results would help to inform about CO evolution even during the cooling process of charcoal.